The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/cbdd.13652
|View full text |Cite
|
Sign up to set email alerts
|

Sertraline/ICG‐loaded liposome for dual‐modality imaging and effective chemo‐photothermal combination therapy against metastatic clear cell renal cell carcinoma

Abstract: A large number of chemotherapeutic drugs, utilized in the treatment of advanced metastatic clear cell renal cell carcinoma, are typically prone to poor biocompatibility, lack of targeting specificity, and high toxicity, which mostly leads to unsatisfactory clinical outcomes. As a new drug delivery pathway, nanoliposomes have the advantages of simplifying metabolism, reducing drug side‐effects, and providing specific targeting, which can potentially improve the therapeutic effect toward tumor therapy. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Although this study focused on ICG liposomes, we note that ICG transfer to albumin has been observed for a related solid nanoparticle formulation and is thus likely to occur with many types of nanoscale ICG formulations. , With regard to phototherapeutics, ICG nanoparticles have been investigated for photothermal therapy, , photodynamic therapy, , and light-triggered drug release. , There is literature evidence that the geometric location of a photosensitizer relative to a liposome membrane (i.e., photosensitizer embedded in the membrane or protruding into the aqueous solution) can affect the rate and extent of light-triggered liposome leakage, and we were curious to learn if ICG transfer to albumin would diminish the extent of NIR light-activated membrane disruption and subsequent content leakage. Therefore, we conducted experiments that measured the NIR light-triggered leakage of aqueous contents from 1,2-dipalmitoyl- sn -glycero-3-phosphocholine (DPPC) liposomes that also contained ICG as the light-absorbing trigger. ,,,,, DPPC liposomes are thermally responsive, and they leak when heated close to their transition temperature of ∼41 °C. Not only does the embedded ICG provide a source of photothermal heating when irradiated with NIR light, it also acts as a photosensitizer to generate reactive oxygen species that can induce phospholipid oxidation and increased liposome membrane permeability. ,,,, …”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although this study focused on ICG liposomes, we note that ICG transfer to albumin has been observed for a related solid nanoparticle formulation and is thus likely to occur with many types of nanoscale ICG formulations. , With regard to phototherapeutics, ICG nanoparticles have been investigated for photothermal therapy, , photodynamic therapy, , and light-triggered drug release. , There is literature evidence that the geometric location of a photosensitizer relative to a liposome membrane (i.e., photosensitizer embedded in the membrane or protruding into the aqueous solution) can affect the rate and extent of light-triggered liposome leakage, and we were curious to learn if ICG transfer to albumin would diminish the extent of NIR light-activated membrane disruption and subsequent content leakage. Therefore, we conducted experiments that measured the NIR light-triggered leakage of aqueous contents from 1,2-dipalmitoyl- sn -glycero-3-phosphocholine (DPPC) liposomes that also contained ICG as the light-absorbing trigger. ,,,,, DPPC liposomes are thermally responsive, and they leak when heated close to their transition temperature of ∼41 °C. Not only does the embedded ICG provide a source of photothermal heating when irradiated with NIR light, it also acts as a photosensitizer to generate reactive oxygen species that can induce phospholipid oxidation and increased liposome membrane permeability. ,,,, …”
Section: Results and Discussionmentioning
confidence: 99%
“…The half-life for ICG transfer from gel-phase DPPC liposomes is ∼3 min at 22 °C. This ICG transfer process has been observed with lipid core nanoparticles, , but it seems to have not been considered by most published studies (perhaps all of them) that use ICG liposomes. , Unlike ICG, the classic lipophilic cyanine dyes such as DiI 20(5) with two long hydrocarbon chains do not transfer from liposomes or related lipid core nanoparticles to external BSA, thus, it is not accurate to assume that ICG exhibits the same phase transfer behavior as the classic lipophilic cyanine dyes The presence of 20% α-tocopherol in ICG liposomes helps retain the ICG in the membrane (presumably by forming favorable aromatic stacking interactions) and inhibits ICG photobleaching.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome this impasse, Lei et al. [69] synthesized a nanoliposome containing sertraline and indocyanine green (ICG), called Ser / ICG @ Lip, with the aim of increasing the concentrations administered and avoiding undesirable side effects. This technology offers a new drug delivery pathway in reason of it's targeted-specific pharmacodynamics and simplified pharmacokinetics that may improve the therapeutic effect towards tumor therapy [ 70 , 71 ] In addition, here we have identified more than thirteen instances of synergism with other drugs that could improve therapeutic regimens, reducing toxicity and side effects.…”
Section: Discussionmentioning
confidence: 99%
“…The primary VX2 orthotopic HCC models were established, and the successful models were con rmed by MRI (Fig 6b). Owing to the side-effects of high ICG concentration (up to 0.5 mg/kg), including fever, shock, and allergy [33][34][35], the working concentration of nanoICG was investigated via intravenous injection. Delightfully, nanoICG exhibited a superior uorescent ability relative to free ICG at a low concentration of 0.08 mg/kg (Fig.…”
Section: Evaluation Of the Navigation Performance Of Shift Nanoicg In Rabbit Ear-bearing Subcutaneous Vx2 Modelsmentioning
confidence: 99%